Clinical and psychosocial functioning in adolescents and young adults with anorectal malformations and chronic idiopathic constipation. Issue 6 (2nd April 2013) - Athanasakos, E. P.; Kemal, K. I.; Malliwal, R. S.; Scott, S. M.; Williams, N. S.; Aziz, Q.; Ward, H. C.; Knowles, C. H.
<x xml:space="preserve">Abstract</x> Background Faecal incontinence (FI) and constipation occur following corrective surgery for anorectal malformations (ARMs) and in children or adults with chronic constipation without a structural birth anomaly (chronic idiopathic constipation, CIC). Such symptoms may have profound effects on quality of life (QoL). This study systematically determined the burden of FI and constipation in these patients in adolescence and early adulthood, and their effect on QoL and psychosocial functioning in comparison with controls. Methods Patients with ARMs or CIC were compared with age‐ and sex‐matched controls who had undergone appendicectomy more than 1 year previously and had no ongoing gastrointestinal symptoms. Constipation and FI were evaluated using validated Knowles–Eccersley–Scott Symptom (KESS) and Vaizey scores respectively. Standardized QoL and psychometric tests were performed in all groups. Results The study included 49 patients with ARMs (30 male, aged 11–28 years), 45 with CIC (32 male, aged 11–30 years) and 39 controls (21 male, aged 11–30 years). The frequency of severe constipation among patients with ARMs was approximately half that seen in the CIC group (19 of 49 versus 31 of 45); however, frequencies of incontinence were similar (22 of 49 versus 21 of 45) (P < 0·001 versus controls for both symptoms). Physical and mental well‐being were significantly reduced in both ARM and CIC groups compared with controls (P = 0·001 and P = 0·015 respectively), with generally worse scores among patients with CIC. Both were predicted by gastrointestinal symptom burden (P < 0·001). There were no statistically significant differences in state or trait psychiatric morbidity between groups. Conclusion FI and constipation are major determinants of poor QoL in adolescents and young adults with ARMs and in those with CIC.